Nonlinear winter atmospheric circulation response to Arctic sea ice concentration anomalies for different periods during 1966–2012. (May 2015) - Semenov, V A; Latif, M
Abstract The early 21st century was marked by several severe winters over Central Eurasia linked to a blocking anti-cyclone centered south of the Barents Sea. Severe winters in Central Eurasia were frequent in the 1960s when Arctic sea ice cover was anomalously large, and rare in the 1990s featuring considerably less sea ice cover; the 1960s being characterized by a low, the 1990s by a high phase of the North Atlantic Oscillation, the major driver of surface climate variability in Central Eurasia. We performed ensemble simulations with an atmospheric general circulation model using a set of multi-year Arctic sea ice climatologies corresponding to different periods during 1966–2012. The atmospheric response to the strongly reduced sea ice cover of 2005–2012 exhibits a statistically significant anti-cyclonic surface pressure anomaly which is similar to that observed. A similar response is found when the strongly positive sea ice cover anomaly of 1966–1969 drives the model. Basically no significant atmospheric circulation response was simulated when the model was forced by the sea ice cover anomaly of 1990–1995. The results suggest that sea ice cover reduction, through a changed atmospheric circulation, considerably contributed to the recent anomalously cold winters in Central Eurasia. Further, a nonlinear atmospheric circulation response to shrinking sea ice cover is suggested that depends on the background sea ice cover.